Mechanical Morphological And Rheological Properties Of Polyamide 6 Organo-Montmorillonite Nanocomposites. - Chow, W.S.; Mohd Ishak, Z.A. (2007)
Polyamide (PA6) nanocomposites containing 4 wt% organo-montmorillonite (OMMT) were melt-compounded followed by injection molding.